An analysis of the tensile properties of nanofiber mats. (2nd September 2015) - Wan, Lynn Yuqin; Wang, Hongbo; Gao, Weidong; Ko, Frank
Abstract: Nanofibers have gained increasing attention because of their potential for a wide range of applications. In order to fully exploit the potential of nanofibers, there is a need to understand the relationship between the mechanical properties, especially tensile properties, of an individual nanofiber and that of nanofiber assemblies. In this study, we examined the relationship between a single nanofiber and a nanofiber mat formed by randomly oriented nanofibers through geometric analysis. The analysis showed that the tensile strength of a randomly oriented nanofiber mat is a function of fiber packing density (porosity), test specimen dimension (width to length ratio), and the tensile strength of a single nanofiber. Similar relationship can also be derived for the elastic modulus of individual nanofibers and that of the nanofiber mats. Parametric study was carried out using this fabric geometry model and the applicability of the model was evaluated using published experimental data. Graphical abstract: Highlights: A geometric analysis is conducted on nanofiber nonwoven unit cell. Theoretical models relate the tensile strength, specific strength and modulus of an individual nanofiber to those of nanofiber nonwoven mat are established. Effects of porosity and size of test specimen on the tensile strength of nanofiber nonwoven mats are studied.